2021
DOI: 10.1038/s41420-021-00448-6
|View full text |Cite
|
Sign up to set email alerts
|

CircHIPK3 regulates the autophagy and apoptosis of hypoxia/reoxygenation-stimulated cardiomyocytes via the miR-20b-5p/ATG7 axis

Abstract: Autophagy and apoptosis are involved in myocardial ischemia/reperfusion (I/R) injury. Research indicates that circular RNA HIPK3 (circHIPK3) is crucial to cell autophagy and apoptosis in various cancer types. However, the role of circHIPK3 in the regulation of cardiomyocyte autophagy and apoptosis during I/R remains unknown. Our study aimed to examine the regulatory effect of circHIPK3 during myocardial I/R and investigate its mechanism in cardiomyocyte autophagy and apoptosis. Methods and results. The express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…The H/R model was established by referring to the previous method [ 17 ]. HL-1 cells from the Chinese Academy of Sciences (Shanghai) were cultured in Dulbecco’s Modified Eagle Medium (DMEM) (Gibco-BRL, Grand Island, NY) at 37°C with 5% CO 2 , and seeded in the logarithmic growth phase into 24-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…The H/R model was established by referring to the previous method [ 17 ]. HL-1 cells from the Chinese Academy of Sciences (Shanghai) were cultured in Dulbecco’s Modified Eagle Medium (DMEM) (Gibco-BRL, Grand Island, NY) at 37°C with 5% CO 2 , and seeded in the logarithmic growth phase into 24-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Qiu and colleagues proved that, in myocardial cells, circular RNA HIPK3 (circHIPK3) regulated the autophagy and apoptosis of hypoxia/reoxygenation-stimulated cardiomyocytes through the miR-20b-5p/Atg7 axis. 49 Tang and colleagues found that long noncoding RNA HOTAIR regulated autophagy through the miR-20b-5p/Atg7 axis in hepatic ischemia/reperfusion injury in the liver. 50 Study in breast cancer indicated that rutin restrained the growth and metastasis of mouse breast cancer cells by regulating the miRNA-129-1-3p-mediated calcium signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-20b-5p plays an important role in mediating cardiomyocytes apoptosis via the HIF-1 α/NF- κ B pathway ( Zhou et al, 2020 ). And circHIPK3 acting as miR-20b-5p sponge could accelerate cardiomyocyte autophagy and apoptosis during myocardial I/R injury ( Qiu et al, 2021 ). Reportedly, miR-27a expression is upregulated in patients with CHD, and its expression level is remarkable correlated with the severity of coronary artery stenosis, which can be used as a biomarker of CHD ( Babaee et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%